2022
DOI: 10.1177/02692163211073939
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein and white blood cell count are adverse prognostic markers for patients with advanced cancer on parenteral nutrition in a palliative care unit setting: A retrospective cohort study

Abstract: Background: Parenteral nutrition is controversial in patients with advanced cancer. Nevertheless, this treatment is common practice near the end of life. Aim: We aimed to identify factors which were associated with the outcome of patients on parenteral nutrition at an academic tertiary palliative care unit. Design: In this retrospective cohort study patients were assigned to two groups according to parenteral nutrition treatment. Inferential statistics were used to assess whether the dynamics of laboratory var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Based on their findings, they suggested a systematic use of the CRP/ albumin score before initiating PN (17). Other studies have also shown that for patients receiving PN, an increase in CRP, as well as white blood cell count and worsening of renal function parameters, are linked to a worse outcome (18,19).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Based on their findings, they suggested a systematic use of the CRP/ albumin score before initiating PN (17). Other studies have also shown that for patients receiving PN, an increase in CRP, as well as white blood cell count and worsening of renal function parameters, are linked to a worse outcome (18,19).…”
Section: Discussionmentioning
confidence: 97%
“…With regard to inflammatory activity, higher levels of CRP were shown to be significantly associated with a negative outcome in terms of OS in different patients receiving PN (17). However, there is a lack of predictive markers that might help in the decision of suspending PN in the palliative setting (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…13 However, Japanese people have a cultural tendency to avoid expressing their intentions clearly and understand others' intentions by reading the context. 14,15 This may reduce opportunities of dialogue with others about one's value, which results in a lack of understanding about the experience of dialogue. Thus, clarifying how dialogue with others, a central element of ACP, is experienced may provide deeper insights into the ACP process and may facilitate the process effectively.…”
Section: Introductionmentioning
confidence: 99%